Who was "James"? essays on the letter's authorship and provenance : resulting from a conference on the occasion of Oda Wischmeyer's 75th birthday - Who Was "James"? Challenging Concepts of Epistolary Authorship: Conference on the Occasion of Oda Wischmeyer’s 75th Birthday 2019 Münster (Westf); Becker, Eve-Marie 1972-; Jónsson, Sigurvin Lárus; Luther, Susanne 1979-; Wischmeyer, Oda 1944-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
Cover -- Title -- Preface -- Table of Contents -- Eve-Marie Becker, Sigurvin Lárus Jónsson, Susanne Luther - Who was 'James'? Profiling the Epistolary Author and His Provenance. Introduction to the Volume -- 1. Heuristics, Tools and Methods of Profiling 'James' -- Niclas Förster - "Elia war ein Mensch uns gleichgeartet" (Jak 5,17): Jakobus, Elia und das Gebet des Gerechten in der Perspektive des Jakobusbriefes -- Susanne Luther - Profiling the Author of the Letter of James: Dealing with Traditions in the Light of Epistolary Authorship Conceptions -- Eve-Marie Becker - Wer ist "Jakobus"? Ein typologischer Blick im Rahmen der frühchristlichen Briefkultur -- Thomas Johann Bauer - Der Jakobusbrief und das Bild des Jakobus im Kontext antiker und frühchristlicher Epistolographie -- Clarissa Breu - Prosopopöie im Jakobusbrief aus dekonstruktiver Perspektive -- Christine Ganslmayer - Der Autor des Jakobusbriefs aus linguistischer Perspektive -- 2. The Letter of James in Current Exegesis and Commentary Work -- Karl-Wilhelm Niebuhr - Wer war "Jakobus" in den Augen seiner Leser? Zu meinem Ansatz der Kommentierung des Jakobusbriefs im EKK -- Oda Wischmeyer - Who was "James"? Der Herrenbruder, "ein Namenloser aus den Vielen", ein "role model" oder ein frühchristlicher Lehrer mit Namen Iakōbos? Die Neukommentierung des Jakobusbriefes für Meyers Kritisch- Exegetischen Kommentar -- John S. Kloppenborg - The Author of James and His Lexical Profile -- Eve-Marie Becker -Σοφία ἂυωϴεν versus ἂυω кλῆơ℩ ? Jas 3:15, 17 and Phil 3:14 in Comparison -- 3. The Letter of James and Ancient Literary Criticism -- George Hinge - The Hexameter in James 1:17: Metrical Forms in Graeco-Roman Prose Literature Between Emulation and Quotation -- Oda Wischmeyer - Scriptural Classicism? The Letter of James as an Early Christian Literary Document -- Alicia J. Batten - James the Dramatist.
"This volume takes up the current scholarly debate on the literary profile and the author of the Letter of James. The approach reaches beyond the conventional historical quest for James' epistolary authorship and intellectual provenance by combining observations about the explicit, the implicit, the historical, and the literary author with studies on style, rhetoric, literary criticism, genre criticism and literary history, religious profiles, literary patterns of authorship, and communicative structures. The essays of this volume present new insights into James' literary concept and multifaceted authorial profile based on the latest research in ancient (epistolary) author-literature, provide new methodological perspectives on early Christian epistolary authorship, and situate the Letter of James within the context of an emerging Christ-believing literary culture." --Provided by publisher
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Criticism, interpretation, etc; Authors and publishers-United States-History; Authorship-Social aspects; Electronic books; Konferenzschrift -- 2019 -- Münster; Festschrift